Pengaruh Persepsi Kemudahan Penggunaan dan Kepercayaan Terhadap Minat Menggunakan Aplikasi Dompet Digital LinkAja - Arif Maulana Nizar; Abdul Yusuf (Universitas Batanghari, 2022)
This study aims to determine the effect of perceived ease of use on interest in using the LINKAJA digital wallet application, to determine the effect of trust on interest in using the LINKAJA digital wallet application. And to find out together the effect of perceived ease of use and trust on interest in using the LINKAJA digital wallet application. The research method uses descriptive and verification with a quantitative approach. With a sample of 384. The data analysis technique used is using path analysis with partial and simultaneous hypothesis testing.The results of this study are that there is a significant correlation between the perceived ease of use and trust variables of 0.540. The perceived ease of use variable has a positive and partially significant effect on interest in using the LinkAja digital wallet application by 12.9%. The variable of perception of trust has a positive and partially significant effect on interest in using the LinkAja digital wallet application by 12.6%. Taken together, the perceived ease of use and trust variables have a simultaneous positive and significant effect on interest in using the LinkAja digital wallet application by 74.6%..